2018
DOI: 10.1016/j.rmed.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Does Continuous Positive Airway Pressure (CPAP) treatment of obstructive sleep apnoea (OSA) improve asthma-related clinical outcomes in patients with co-existing conditions?- A systematic review

Abstract: Asthmatics with co-existing OSA can experience improved quality of life with CPAP treatment. This effect appears more pronounced in severe OSA or poorly controlled asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 34 publications
0
20
1
1
Order By: Relevance
“…In this study, we found that CIH exposure significantly increased airway responsiveness in mice. It is noteworthy that treatment with continuous positive airway pressure (CPAP) could not ameliorate FEV1 and AHR in asthma patients with OSA in a recent systematic review (Davies et al, 2018). In contrast, our results demonstrated that combining Dex with SB239063 promoted the depression of airway resistance.…”
Section: Discussioncontrasting
confidence: 64%
“…In this study, we found that CIH exposure significantly increased airway responsiveness in mice. It is noteworthy that treatment with continuous positive airway pressure (CPAP) could not ameliorate FEV1 and AHR in asthma patients with OSA in a recent systematic review (Davies et al, 2018). In contrast, our results demonstrated that combining Dex with SB239063 promoted the depression of airway resistance.…”
Section: Discussioncontrasting
confidence: 64%
“…One study reported a decreased rate of FEV 1 decline in asthmatic patients treated with CPAP [136], but the majority of studies agree on unchanged pulmonary function after CPAP. A recent systematic review pointed out that results of different studies do not allow to document a definite improvement in asthma control, although a positive effect of CPAP treatment seems to occur in patients with severe OSA or poorly controlled asthma [151].…”
Section: Common Comorbidities In Osa Patientsmentioning
confidence: 99%
“…The association between OSA and respiratory symptoms is well established [ 12 , 29 ]. This study adds evidence of an association between elevated OSA risk and a decline in lung function in the previous 10 years, and that the MAP index may be useful to identify these subjects.…”
Section: Discussionmentioning
confidence: 99%